The relationship between the skin microecology and the skin barrier - LIN Tianyi; CHEN Jiaoquan; OU Shanshan; WU Weihong; ZOU Hui; CHEN Ziyan; PENG Liqian; CHEN Quan; LI Huaping; ZHU Huilan (Pifu-xingbing zhenliaoxue zazhi)
With the development of metagenomics sequencing and spatial transcriptomics, the door to the "microscopic world" of the skin surface has gradually been opened, and the "inhabitants" on the "habitat" of the skin have gradually become well-known. These microbial inhabitants contribute greatly to the homeostasis of the skin microenvironment by communicating with the host cells and maintaining the structural integrity and function of the skin barrier. The skin barrier does not only provide a living environment for epidermal microorganisms, but also regulates the composition of the skin microbial community in terms of physics, chemistry and immunity. Therefore, disruption of the skin barrier or imbalance of the skin microbiome can profoundly impact the behavior of host cells. The colonization of pathogenic bacteria and the loss of microbial diversity will activate the molecular signaling pathways that mediate the immune inflammatory response, resulting in the production and aggravation of many skin diseases, such as atopic dermatitis, acne, psoriasis, solar diseases, etc. Based on the current research status in skin microbiota, this article discusses the process of the interaction between skin microbiota and skin barrier, as well as the relationship between skin barrier damage and skin microbiota imbalance in the course of diseases.